Absolute and relative chronology of a complex alpine game drive site (5BL148), Rollins Pass, Colorado - Meyer, Kelton A., author; LaBelle, Jason M., advisor; Glantz, Michelle M., committee member; Breidt, F. Jay, committee member (Colorado State University. Libraries, 2019)
Native American alpine game drive sites are recognized along major mountain travel corridors in Colorado's Southern Rockies. The Rollins Pass project area, located east of Winter Park, represents the densest concentration of alpine game drive sites in North America. Game drives at Rollins Pass vary in terms of size, frequency and diversity of features and artifacts, but also landform context. Past game drive research at Rollins Pass and elsewhere in the Colorado Front Range demonstrates that hunter-gatherer groups reoccupied some sites for centuries and even millennia, creating an amalgamation of material culture over the course of time. However, chronological reconstructions in alpine environments are limited by poor preservation, lacking stratigraphy, and the ephemeral nature of hunter-gatherer occupations at high altitudes. This thesis considers an investigation of the largest game drive at Rollins Pass, 5BL148, with a focus on chronology reconstruction. A relative occupation span is provided with an analysis of chipped stone tools and jewelry. Lichenometry is used to determine the age of lichen colonization events on stone walls, and radiocarbon dates on faunal remains and charcoal are used as absolute chronological measures. A spatial analysis of the artifact and feature assemblage is further used to identify evidence for distinct or temporally overlapping occupation episodes. The results indicate that 5BL148 represents a palimpsest of hunter-gatherer occupations, beginning in the Early Archaic era and ending in the Protohistoric era.
Keywords: archaeology; hunter-gatherer; prehistoric; chronology; alpine; hunting